Pengetahuan dan Sikap Siswi SMA Muhammadiyah 3 Palembang dan Siswi SMA Negeri 3 Palembang tentang Leukorrhea - Trisnawati, Trisnawati; Arsyad, Kiagus Muhammad; Susanti, Rizki Amalia (Syifa'Medika, 2012)
Leukorrhea